2020
DOI: 10.1002/da.23082
|View full text |Cite
|
Sign up to set email alerts
|

Insecure attachment and maladaptive emotion regulation mediating the relationship between childhood trauma and borderline personality features

Abstract: Background: Previous studies suggested that childhood trauma is an important etiologic factor for the development of borderline personality disorder (BPD). Moreover, insecure attachment and maladaptive emotion regulation (ER) might be related to childhood trauma and BPD. This study was aimed to explore the relationships among childhood trauma, insecure attachment, maladaptive ER, and BPD features. Methods: A cohort of 637 patients with psychological disorders completed a series of psychometric instruments such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 62 publications
5
31
0
9
Order By: Relevance
“…Childhood abuse is suggested to lead to insecure attachment patterns, such as anxious or avoidant attachments, which may further contribute to psychopathology development in a wide range of disorders [52][53][54][55][56]. This is particularly well established for BPD: previous work supports the presence of insecure attachment in BPD patients and suggests that core symptoms of the disorder may arise in relation to this aspect [57][58][59][60][61][62][63][64]. Similarly, although research is still scarce, there are some preliminary data suggesting a link between ADHD and insecure attachment [65,66].…”
Section: Introductionmentioning
confidence: 98%
“…Childhood abuse is suggested to lead to insecure attachment patterns, such as anxious or avoidant attachments, which may further contribute to psychopathology development in a wide range of disorders [52][53][54][55][56]. This is particularly well established for BPD: previous work supports the presence of insecure attachment in BPD patients and suggests that core symptoms of the disorder may arise in relation to this aspect [57][58][59][60][61][62][63][64]. Similarly, although research is still scarce, there are some preliminary data suggesting a link between ADHD and insecure attachment [65,66].…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, a growing number of studies have recently started to explore the association between childhood maltreatment and different psychopathological outcomes with the perspective of considering attachment as a mediator of the relationship (Chatziioannidis et al, 2019; Kong et al, 2018; Pearce et al, 2017; Tibi et al, 2020; Van Assche et al, 2020). With respect to the interrelation between childhood maltreatment, attachment and personality dysfunction, the few studies existing in the field have been conducted with the general population (Crow & Levy, 2019; Fossati et al, 2016), a clinical sample with mood disorders (Baryshnikov et al, 2017) and heterogeneous clinical samples (Cohen et al, 2017; Peng et al, 2020). In all cases, insecure attachment seemed to mediate the relationship between childhood trauma and personality dysfunctional traits and, in most cases, borderline personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…In our multivariate models, the effect of cumulative SLEs on affective symptoms appeared independent of attachment, suggesting a direct effect of adverse life experiences on affective regulation, for example, a direct effect on the axis of stress that causes affective symptoms. In this sense, evidence has emerged in the literature that there are direct psychopathological pathways between childhood abuse and borderline symptoms, not related to attachment, and involving or not emotional dysregulation ( 57 ). Fonagy and Luyten have suggested that the impact of SLEs on emotional dysregulation is a consequence of increased arousal and a lowered threshold for attachment and for deactivation of controlled mentalization ( 13 ).…”
Section: Discussionmentioning
confidence: 99%